Development of Innovative Tools in Global Financial Markets - Danylkiv, Khrystyna; Dropa, Yaroslav; Petyk, Marta; Hembarska, Nataliia; Siryk, Zinoviy (Journal of Vasyl Stefanyk Precarpathian National University, 2022)
The purpose of the article is to study the theoretical foundations and develop practical recommendations for improving the process of functioning financial instruments in global financial markets. The article reveals the essence and characterizes the components of the modern global financial market, defines its role in the development of the national economy, and the peculiarities of its formation in the conditions of the expansion of innovative digital technologies. The essence of financial market instruments is revealed and the need to improve their investment qualities to the requirements of modern economic conditions is argued. Financial instruments that are in circulation on the financial market are systematized according to several features. Considerable attention is paid in the work to the circulation of innovative financial instruments, the main feature of which is a high level of risk. Peculiarities of the formation and functioning of derivative financial instruments were studied, and the essence and specifics of the use of credit notes on the stock market were revealed. The mechanism of circulation of credit notes is presented and their main functional features are defined. It is noted that the issuance and sale of credit notes enable borrowers to mobilize funds on the global financial markets, and improve their investment image in the international market through the formation of a high credit rating from global financial institutions. The peculiarities of cryptocurrency circulation on the global financial market from the point of view of today's most popular innovative financial instrument are revealed; the authors emphasized the dual nature of cryptocurrencies, as it has the properties inherent in stock market instruments and features that characterize financial pyramids. The dynamics of the development of the global cryptocurrency market over a long period have been analyzed. The peculiarities and problems of regulating the circulation and taxation of cryptocurrencies in Ukraine and the world are highlighted. The formation and specifics of circulation on the domestic financial market of bitcoin derivatives as a new financial instrument are described. The authors also focused attention on the spread of negative trends in the circulation of cryptocurrencies and substantiated possible ways to overcome them. The article analyzes the functioning and development of the option certificates and derivatives market in Ukraine in terms of stock and over-the-counter markets. The main factors restraining their development include inadequate regulatory and legal support, the small size of the markets, and a small number of tools used in them.